Legs of male fiddler crabs evolved to compensate for claw exaggeration and enhance claw functionality during waving displays. (1st November 2018) - Bywater, Candice L.; Wilson, Robbie S.; Monro, Keyne; White, Craig R.
Abstract: Many exaggerated morphological traits evolve under sexual selection. However, the optimal level of exaggeration is dictated by a trade‐off between natural and sexual selection, representing a balance between its benefits and associated costs. Male fiddler crabs wave an enlarged major claw during behavioural displays that eliminates the need for direct combat, and determines courtship outcomes. The outcomes of these displays often depend on claw size, exposing males to selection for larger claws to improve mating and combat success. Applying phylogenetic comparative methods to 27 fiddler crab species, we examined the evolution of major claw morphologies, leg morphologies, and waving displays to determine whether these traits coevolved to optimise functioning of the exaggerated claw, or to mitigate potential metabolic or locomotor costs. We found legs to be sexually dimorphic, with males having longer legs than females. Legs were also longer in species that waved laterally rather than vertically, in species with larger major claws, and in species whose major claws were relatively elongate. These results suggest that leg morphology has coevolved with claw enlargement to enhance functionality of the major claw during waving displays, in addition to compensating for any negative effects of claw size.